Environmentally Responsible Purchase Intention in Pacific Alliance Countries: Geographic and Gender Evidence in the Context of the Covid-19 Pandemic - Escobar-Farfan, M (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
The objectives of this research were: (1) to examine the influence of environmental awareness (EA), sustainable consumption (SC) and social responsibility (SR) on the environmentally responsible purchase intention (ERPI) of consumers in the member countries of the Pacific Alliance, namely, Chile, Colombia, Mexico and Peru; and (2) to analyze whether there is a moderating effect related to the country of residence and gender of the consumer. The study was conducted under a quantitative and cross-sectional approach. The sample consisted of 1646 consumers: 24.4% from Peru (n = 402), 25.4% from Mexico (n = 418), 26.1% from Colombia (n = 401) and 24.1% from Chile (n = 397). Data analysis and hypothesis testing were performed using a multigroup Structural Equation Model (SEM). The results show a positive influence among environmental awareness (EA), sustainable consumption (SC) and social responsibility (SR) on environmentally responsible purchase intention (ERPI). Gender and country of residence were also shown to be moderating variables in these relationships. In conclusion, it can be affirmed that the participants of this study recognize the importance of acquiring environmentally friendly products. Among them, the female population is more aware of this issue. It is recommended new business models be created to provide products and services oriented to this market according to consumers’ tastes, desires and purchasing preferences; the proposals they have should be friendly to the environment and to society. © 2023 by the authors.